Exploring the plexus of context and consequences: An empirical test of a theory of disaster vulnerability. (September 2015) - Dückers, Michel; Frerks, Georg; Birkmann, Jörn
Abstract: What determines the disaster vulnerability of countries? In this study a theoretical model was tested, linking disaster vulnerability to physical hazards and cultural and historical factors. Associations between the World Vulnerability Index and Hofstede's cultural dimensions scores were explored using quantitative methods, while taking exposure to natural hazards into account. Data of 60 countries could be matched. Less exposed countries in this sample are significantly less vulnerable. Culturally, particularly countries with a lower power balance and a higher level of individualism are less vulnerable as well; two features linked to higher levels of wealth. Approximately 70% of the variance in vulnerability could be explained in this way. These results should, however, be interpreted with some caution as longitudinal data were unavailable and disaster vulnerability itself may be seen as a cultural derivate, making it impossible to clarify causal mechanisms. Despite these and other limitations, the study points at interesting associations that, firstly, should be expanded and replicated in larger samples, allowing more advanced analysis, and secondly, encourage a more thorough examination of different local contexts and cross-level interactions than was possible in this exploratory endeavor.